Self medicated antibiotics in Bangladesh: a cross-sectional health survey conducted in the Rajshahi City - Biswas, Mohitosh; Roy, Manobendro Nath; Manik, Md Imran Nur; Hossain, Md Shahid; Tapu, SM Tafsirul Alam; Moniruzzaman, Md; Sultana, Sharmin (BMC public health, 2014)
Antibiotic self medication is highly prevalent in the developing countries due to easy availability and poor regulatory controls for selling these drugs. The purpose of this study was to evaluate the prevalence of self-medication with antibiotics for the treatment of various diseases by the peoples of Rajshahi city in Bangladesh. A cross-sectional survey was conducted to the patient's (n = 1300) at eight locations of Rajshahi city in Bangladesh from March to April, 2014. The locations were selected by convenience and the study population within each study area was randomly selected. The survey was self-administered and included questions pertaining to self medicated drugs and antibiotic usage patterns as well. Data were analyzed using descriptive statistics. It was found that 347 (26.69%) out of 1300 participants experienced self medication with antibiotics. Over fifty percent of the patients studied were between the ages of 21-30 years with 83.57% of them being males and 16.43% females. The highest percentage of self medicated antibiotics was metronidazole (50.43%) followed by azithromycin (20.75%), ciprofloxacin (11.53%), amoxicillin (10.37%) and tetracycline (7.49%) respectively. The key reasons for the self medication of antibiotics was the pre-experience (45.82%), suggestions from others (28.24%) and knowledgeable of the antibiotics (16.14%). The perceived symptoms to purchase the antibiotics independently was dysentery, diarrhea and food poisoning (36.02%), cold, cough and fever (28.24%), infection (12.97%), dental carries and toothache (9.22%), irritable bowel syndrome (3.46%), acne (4.32%), ear and throat pain (2.31%). The duration of maximum antibiotics usage was ranges between 0-10 years. Only 4.32% patient's used self medicated antibiotics longer than 10 years. The patient's compliance for self medication of antibiotics varies from excellent to no comments whereas only 6.92% patients reported side effects for the self medication of antibiotics. The results of this study confirm that antibiotic self-medication is a relatively frequent problem in Bangladesh. Drug Administration of Bangladesh should implement the regulatory controls immediately on the distribution and selling of antibiotics in order to reduce the frequency of antibiotic misuse.